How to Improve Interactions between Police and the Mentally Ill - Krameddine, Yasmeen I.; Silverstone, Peter H. (Frontiers in Psychiatry, 2015)
There have been repeated instances of police forces having violent, sometimes fatal, interactions with individuals with mental illness. Police forces are frequently first responders to those with mental illness. Despite this, training police in how to best interact with individuals who have a mental illness has been poorly studied. The present article reviews the literature examining mental illness training programs delivered to law enforcement officers. Some of the key findings are the benefits of training utilizing realistic “hands-on” scenarios, which focus primarily on verbal and non-verbal communication, increasing empathy, and de-escalation strategies. Current issues in training police officers are firstly the tendency for organizations to provide training without proper outcome measures of effectiveness, secondly the focus of training is on changing attitudes although there is little evidence to demonstrate this relates to behavioural change, and thirdly the belief that a mental health training program given on a single occasion is sufficient to improve interactions over the longer-term. Future police training needs to address these issues.